2018
DOI: 10.1186/s12964-018-0289-z
|View full text |Cite|
|
Sign up to set email alerts
|

Conditional ablation of p130Cas/BCAR1 adaptor protein impairs epidermal homeostasis by altering cell adhesion and differentiation

Abstract: Backgroundp130 Crk-associated substrate (p130CAS; also known as BCAR1) is a scaffold protein that modulates many essential cellular processes such as cell adhesion, proliferation, survival, cell migration, and intracellular signaling. p130Cas has been shown to be highly expressed in a variety of human cancers of epithelial origin. However, few data are available regarding the role of p130Cas during normal epithelial development and homeostasis.MethodsTo this end, we have generated a genetically modified mouse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 40 publications
(59 reference statements)
0
9
0
Order By: Relevance
“…Co-sedimentation and ELISA assays suggested a direct association of CSRP2 with F-actin 44 , 45 . Furthermore, CSRP2 could also sequester the scaffold protein p130Cas at focal adhesions, control lamellipodia formation, and reduce vascular smooth muscle cell motility 18 , 46 . These observations suggested that CSRP2 may be involved in the cytoskeletal regulation and cell motility, processes that are associated with cancer metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Co-sedimentation and ELISA assays suggested a direct association of CSRP2 with F-actin 44 , 45 . Furthermore, CSRP2 could also sequester the scaffold protein p130Cas at focal adhesions, control lamellipodia formation, and reduce vascular smooth muscle cell motility 18 , 46 . These observations suggested that CSRP2 may be involved in the cytoskeletal regulation and cell motility, processes that are associated with cancer metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, Bcar1 was one of the differentially methylated genes identified in the present study. Bcar1 is a vital scaffolding protein that modulates numerous essential cellular processes ( 62 , 63 ). It belongs to the Crk-associated substrate family of scaffolding proteins ( 64 ).…”
Section: Discussionmentioning
confidence: 99%
“…There is increasing evidence that Bcar1 serves a crucial role in cell-extracellular matrix adhesion, tissue homeostasis and pathogenesis of Kaposi's sarcoma-associated herpesvirus ( 65 ). Furthermore, the lack of Bcar1 in some cells may lead to altered integrin signaling, which is reflected by aberrant basal membrane adhesion ( 63 ). This is consistent with the expression of changes in core genes that affect adhesion in Schwann cells after PNI, as shown in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…This study focused on keratinocyte dysfunction in diabetic wounds, as keratinocytes are the main cell type found in the skin. The expression of PCNA was measured as a proliferation marker of keratinocytes [ 18 ], and expressions of TGM1 and LOR were measured as late differentiation markers of keratinocytes [ 19 ]. In addition, we chose HaCaT cells for our experiments because these cells have similar characteristics to epidermal stem cells [ 20 ] and are widely used in the study of the pathophysiology of diabetic foot ulcers [ 21 ].…”
Section: Discussionmentioning
confidence: 99%